Postoperative Gait Mechanics After Total Hip Arthroplasty: A Systematic Review and Meta-Analysis. Issue 11 (November 2018) - Moyer, Rebecca; Lanting, Brent; Marsh, Jacquelyn; Al-Jurayyan, Abdulaziz; Churchill, Laura; Howard, James; Somerville, Lyndsay
Abstract : Background: Total hip arthroplasty is recommended by clinical practice guidelines for improving pain in patients with severe hip osteoarthritis, yet functional limitations may persist postoperatively. The effects of the surgical approach on postoperative gait biomechanics may influence these limitations after total hip arthroplasty but are currently not well established. The purpose of this study was to investigate the differences in postoperative gait biomechanical differences, at early and late follow-up, in patients with hip osteoarthritis who underwent total hip arthroplasty using different surgical approaches. Methods: Four electronic databases were searched from their inception to December 2016. Four pairs of reviewers independently determined study eligibility, rated study quality, and extracted data. Pooled estimates for each meta-analysis were obtained using a random-effects model. Mean differences (MDs) and standardized mean differences (SMDs) were calculated for spatiotemporal, kinematic, and kinetic gait variables at early (⩽3 months) and late (≥6 months) postoperative follow-up. The posterior, anterior, direct lateral, and anterolateral approaches were compared using the mean postoperative differences between approaches, standard deviations, and sample sizes. Results: Nineteen studies (757 participants) were included. Individual and pooled effect sizes for the differences between approaches were inconsistent, with minimal significant differences at early or late follow-up. A significant increase in step length was observed after the posterior approach compared with the anterolateral approach at early (SMD = 0.68, p = 0.035) and late (SMD = 0.46, p = 0.032) follow-up, as well as a significant increase in hip adduction moment after the posterior approach compared with the lateral approach at early follow-up (SMD = 0.70, p = 0.020). Effect sizes ranged from small to very large, but too few studies comparing similar surgical approaches, as well as inconsistent reporting of outcome measures, limited the ability to pool data. Conclusions: These findings suggest little early or late postoperative difference in gait biomechanics between surgical approaches. Although some significant differences between surgical approaches exist, determining whether the reported postoperative gait value differences are clinically meaningful remains a substantial challenge for the interpretation of these findings. Level of Evidence: TherapeuticLevel II . See Instructions for Authors for a complete description of levels of evidence.